Pengaruh Media Sosial, Kepercayaan dan Citra Merek Terhadap Keputusan Pembelian Pada E-Commerce Bukalapak di Kota Batam - Okto Nopita Girsang; Nur Elfi Husda (Komunitas Dosen Indonesia, 2024)
This study aims to determine the influence of social media, trust, and brand image on purchase decisions in Bukalapak e-commerce in Batam City. Utilizing an associative method with a quantitative approach, the population under study consists of consumers actively using Bukalapak Nutrition e-commerce in Batam in 2024. The sample size was determined using the Jacob Cohen formula, resulting in 204 respondents selected randomly through purposive sampling. The data analysis process encompasses several stages, including data quality testing, classical assumption testing, influence testing, and hypothesis testing to assess the significance of each variable's influence, all processed using the SPSS program. The results of the multiple linear regression analysis indicate that social media contributes 18.3% to the variability of purchase decisions, trust contributes 40.8%, and brand image contributes 23.5%. The analysis of the coefficient of determination (R²) shows that 72.9% of the variation in purchase decisions is explained by the combined influence of social media, trust, and brand image. Additionally, the t-test results confirm the partial and significant effects of each variable on purchase decisions. Social media has a t-value of 4.216, greater than the t-table value of 1.971, with a significance value of 0.00 (<0.05), indicating a significant effect on purchase decisions. Trust shows a t-value of 9.465, also greater than the t-table value of 1.971, with a significance value of 0.00 (<0.05), confirming its significant impact. Similarly, brand image has a t-value of 6.408, exceeding the t-table value of 1.971, with a significance value of 0.00 (<0.05), demonstrating a significant effect on purchase decisions.